Long Interleukin-22 Binding Protein Isoform-1 Is an Intracellular Activator of the Unfolded Protein Response - Gómez-Fernández, Paloma; Urtasun, Andoni; Paton, Adrienne W.; Paton, James C.; Borrego, Francisco; Dersh, Devin; Argon, Yair; Alloza, Iraide; Vandenbroeck, Koen (Frontiers in Immunology, 2018)
The human IL22RA2 gene co-produces three protein isoforms in dendritic cells (IL-22 binding protein-1, IL-22BPi2 and IL-22BPi3). Two of these, IL-22BPi2 and IL-22BPi3, are capable of neutralizing the biological activity of IL-22. The function of IL-22BPi1, which differs from IL-22BPi2 through an in-frame 32-amino acid insertion provided by an alternatively spliced exon, remains unknown. We demonstrate that IL-22BPi1 is secreted detectably, but at much lower levels than IL-22BPi2, and unlike IL-22BPi2 and IL-22BPi3, is largely retained in the endoplasmic reticulum (ER). As opposed to IL-22BPi2 and IL-22BPi3, IL-22BPi1 is incapable of neutralizing or binding to IL-22 measured in bioassay or assembly-induced IL-22 co-folding assay. We performed interactome analysis in transfected human cell lines, to disclose the mechanism underlying the poor secretion of IL-22BPi1 and identified GRP78, GRP94, GRP170 and calnexin as main interactors. Structure-function analysis revealed that, like IL-22BPi2, IL-22BPi1 binds to the substrate-binding domain of GRP78 as well as to the middle domain of GRP94. Ectopic expression of wild-type GRP78 enhanced, and ATPase-defective GRP94 mutant decreased, secretion of both IL-22BPi1 and iL-22BPi2, while neither of both affected IL-22BPi3 secretion. Thus, IL-22BPi1 is a bona fide client protein of the ER chaperones GRP78 and GRP94 similar to IL-22BPi. However, in contrast to IL-22BPi2 and IL-22BPi3, IL-22BPi1 activates an unfolded protein response resulting in increased protein levels of GRP78 and GRP94. Cloning of the IL22RA2 alternatively spliced exon into an unrelated cytokine, IL-2, bestowed similar characteristics on the resulting protein. Upon silencing of IL22RA2 expression in natural producer cells, i.e. human immature monocyte-derived dendritic cells, GRP78 levels were significantly reduced, suggesting that native IL22RA2 expression naturally contributes to upregulating levels of GRP78 in these cells. The IL22RA2 alternatively spliced exon was reported to be recruited through a single mutation in the proto-splice site of a Long Terminal Repeat retrotransposon sequence in the ape lineage. Our work suggests that positive selection of IL-22BPi1 was not driven by IL-22 antagonism as in the case of IL-22BPi2 and IL-22BPi3, but by capacity for induction of an UPR response.